Travel Guide for Home – Aspects of Living the Protestant Spirituality in Everyday Life - SIBA, Balázs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
This study reflects on changing everyday habits from a protestant theological perspective. Our faith grows not only in celebration or on Sunday, but also in everyday actions and habits from Monday through Saturday. The study deals with questions such as: Despite our good intentions, why is it so hard to achieve long-term changes in our lives? In what ways should we change in relation to our bad habits? How can God’s justification and sanctification play a role in our spiritual development?